สื่อการสอนออนไลน์ในศตวรรษที่ 21 - เทศน์ธรรม, สมพงษ์ (วารสาร มมร ยศสุนทรปริทรรศน์, 2024)
Teaching in the 21 st century has an important purpose: Provide students with basic knowledge Skills and learning processes and life skills Can be practically applied By promoting and stimulating students to have a desire to learn. That is called having a scientific mind. Cognition occurs critical thinking Problem solving management synthesis creative thinking Work with others, have a network, have interpersonal skills. Through the tools of information technology media Including educational innovations In terms of various types of teaching media The authors summarized it as follows: people, materials (Materials, buildings (Settings), tools and equipment (Tools and Equipments), activities (Activities). Moreover, it is divided into groups, namely teaching media. Large group learning media, small group learning media, distance learning media, and learning media that emphasizes individual progress rates. In summary, various types of media From the past to the present (21 st century) as follows: visual media or graphic materials (Graphics), visual media, projector media, audio media, television media (Television) or, for short, TV (TV) and educational videotapes. , Computer media for education and teaching and multimedia and interactive media which Multi-Media is a media that combines everything of all the media mentioned above. It is a variety of media such as visual media, audio media, material media, graphic media, text media. computer media etc. As for online teaching media in the 21st century via the internet. various websites and through various apps, which can be summarized as follows Apps in the Google network include Google Meet, Google Forms, Google Classroom, Google Sheets, Google Slides. ), Google Docs, Google My Maps, Google Jamboard, Google Drawing (Google-drawings), Google Sites (Google-sites) and Google Cloud (Cloud google). There are also other apps. that is not an app in the Google network is Microsoft Teams app (Microsoft-teams), Zoom meeting online app (Zoom meeting online), Mural app (Mural) and Line video call app (Line Video call)